Enhancing Students' Problem-Solving Abilities: The Role of Project-Based Learning, Problem-Based Learning, and Learning Motivation - Gunawan, Wawan; Atiqoh, Atiqoh; Wiyarno, Yoso; Fatirul, Achmad Noor; Sugiarni, Sugiarni; Mastoah, Imas (FKIP Universitas Lampung, 2025)
Enhancing Students' Problem-Solving Abilities: The Role of Project-Based Learning, Problem-Based Learning, and Learning Motivation. Objective: This study aims to examine the effect of Project-Based Learning (PjBL), Problem-Based Learning (PBL), and learning motivation on students' problem-solving abilities at the secondary education level. Methods: This study uses a quantitative approach with SmartPLS 4 data analysis techniques to test the relationship between the variables involved. The research sample consisted of students at the secondary education level who were divided into three experimental groups. Each group received project-based learning (PjBL), problem-based learning (PBL) interventions, as well as the influence of learning motivation as a factor influencing students' problem-solving abilities. Findings: The results of the study indicate that both PjBL and PBL have a positive and significant effect on students' problem-solving abilities. In addition, learning motivation has also been shown to have an important role in strengthening the development of students' problem- solving abilities. These findings indicate that project-based and problem-based learning can improve students' skills in solving complex problems. Conclusion: The findings of this study provide evidence that Project-Based Learning and Problem-Based Learning methods can be effective alternatives to improve students' problem-solving abilities. Learning motivation also plays a crucial role in supporting the learning process. Therefore, it is important for teachers to create a learning environment that can motivate students to be more active and participate. By combining these two methods, students are expected to develop critical and creative thinking skills, which are very much needed in facing challenges in the real world. Further research is needed to explore other factors that may affect students' problem-solving abilities, such as social and emotional factors. Keywords: PjBL, PBL, problem-solving ability, learning motivation.